Average duration of a forthcoming life as the integrated demographic indicatorand a method of an estimation of a state of health of the population - Mendrina, G. I.; Oleynichenko, V. F. (Bi͡u︡lletenʹ Sibirskoĭ medit͡s︡iny, 2008)
Both in the Russian Federation and in Tomsk area comes to light negative tendencies in population health: low level of indicator ADFL and the tendency of its decrease, lower level of an indicator at men, than at women. Only hardly more than half of men born in 2003 can live till 65 years, and women more than half till 80 years IADFL countrymen considerably below city, there are no bases for optimistic forecast IADFL for men.